ELECTRICAL CONDUCTION IN GeO2 / BaO GLASSES - Nadeem, M. Y.; Wasiq, M. F.; Altaf, M.; Chaudhry, M. A. (Journal of Research (Science), 2004)
The electrical measurements have been carried out in a number of germanate glasses described by the equation x mol % GeO2 + (100-x) mol % BaO. The samples were prepared using melt quench technique. D.C. electrical conduction of the glass specimens at room temperature was studied using the two probe method. The electrical conduction mechanism was found to be Poole-Frenkel. The Poole Frenkel coefficient of barrier lowering was found to lie in the range 5.82x10-5 to 8.45 x 10-5 eV m1/2 V-1/2. The electrical conductivity was found to decrease with the increasing value of the former to modifier weight ratio. The activation energy was also calculated by observing the temperature dependence of the conductivity.